Analisis Tingkat Kerusakan Hutan Mangrove di Desa Palopo Kecamatan Marisa Kabupaten Pohuwato - Koni, Fitriyanti H.; Hamidun, Marini Susanti; Baderan, Dewi Wahyuni K. (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Mangrove is an ecosystem found in coastal areas and is influenced by the ebb and flow of sea water. This ecosystem has ecological, socio-cultural and socio-economic roles. The purpose of this study was to determine the level of damage to mangrove forests. This study used survey and line transect methods. Based on the results of the study in Palopo Village, 13 types of mangroves were found to be included in the station. Among them are, Bruguiera sp, Bruguiera sexangula, Rhizophora apiculata, Rhizophora mucronata, Ceriops tagal, Avicennia lanata, Sonneratia alba, Xylocarpus mollucensis, Lumnitzera racemosa, Calophyllum inophyllum L, Excoecaria agallocha L, Ceriops decandra and Bruguiera plaviflora. In accordance with the Decree of the Minister of Environment Number 201 of 2004 concerning the criteria for mangrove forest damage, the density of trees at stations I and II is included in the damaged category (rare) because the density is <1000 trees. For the canopy cover of mangrove trees, the Excoecaria agallocha L. species at station II obtained a coverage percentage of 50.23%, while the other 11 species obtained a coverage percentage below 50%. Based on the coverage criteria, the mangrove species Excoecaria agallocha L. is included in the good (moderate) category, while the other 11 species are included in the damaged category.